AGENESIS OF MUSCULOCUTANEOUS NERVE AND THE MEDIAN NERVE INNERVATED THE BRACHIAL FLEXORS IN A FEMALE CADAVER – A CASE REPORT - PRIYA G,; NANDHINI S,; NITHYA S,; MAHIMA SOPHIA M,; YUVARAJ M, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The musculocutaneous nerve arises from the lateral cord of brachial plexus that supply the brachial flexor muscles. The variations in the formation of musculocutaneous nerve are common but arising as branches from median nerve is a rare case. During routine dissection for undergraduate medical students in Panimalar medical college hospital and research institute at Chennai, observed agenesis of musculocutaneous nerve and the muscles of anterior compartment of arm was supplied by the branches originated from the median nerve in a female cadaver aged about 65 years old. This variation was found on the left arm and the right arm showed normal course of the nerve. On the left arm, a thin nerve was observed along the lateral side that have originated from the lateral root of median nerve supplied coracobrachialis and is named as the nerve to coracobrachialis. At about 5cm below the formation of median nerve, arise a trunk which descended laterally for about 2cm and then trifurcated. The first branch supplied biceps brachii muscle, the 2nd branch entered brachialis muscle to supply it and 3rd branch descended between biceps brachii and brachialis, and emerged from the lateral border of the tendon of biceps brachii by piercing the deep fascia at about 2-3cm proximal to the bend of the elbow as lateral cutaneous nerve of the forearm. According to this study, injury to the median nerve in the arm may cause clinical findings similar to those of musculocutaneous nerve injury signs like weakness in elbow flexion, atrophy of the biceps brachii and paresthesia at the lateral forearm. Therefore, the knowledge of the present variation may help in clinical practice while doing invasive or surgical procedures and in post-traumatic evaluation of the nerve pathway.